PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK PADA TEMA I ORGAN GERAK HEWAN DAN MANUSIA PADA SISWA KELAS V - NESI, ESTIANA; WAU, MARIA PATRISIA; LAWE, YOSEFINA UGE (Jurnal Citra Pendidikan, 2022)
ABSTRACT The purpose of this study was to determine the improvement of student learning outcomes on the theme 1 Animal and Human Movement Organs in fifth grade students of SDI Rutosoro, Golewa District, Ngada Regency through the application of the guided inquiry learning model. This type of research is classroom action research (CAR) developed by Kemmis and Mc Taggart, which consists of two cycles and each cycle consists of planning, implementing, and observing, and reflecting. The subjects of this study were 6th grade students of SDI Rutosoro. Research data were collected using test techniques and research instruments in the form of a description test. Data were analyzed by quantitative descriptive statistics. The results of the first cycle of action research obtained that the average student learning outcomes in thematic learning theme I of animal and human movement organs was 63.34, with a percentage of 63.34% and was in the fairly good category. In the second cycle, the average student learning outcomes in thematic learning theme I animal and human movement organs were 94.83 with a percentage of 94.83%. And is in a predetermined category, namely the results criteria with a percentage of 80-100%. the increase from cycle I to cycle II was 31.43%. Based on the data above, it can be concluded that the application of the guided inquiry learning model can improve the learning outcomes of the fifth grade students of SDI Rutosoro for the 2021/2022 academic year.